EDEN ISS: A SIMULATION TESTBED TO AN ADVANCED XPLORATION DESIGN CONCEPT FOR A GREENHOUSE FOR MOON AND MARS - Imhof, Barbara; Schlacht, Irene Lia; Waclavicek, René; Schubert, Daniel; Zeidler, Conrad; Vrakking, Vincent; Hoheneder, Waltraut; Hogle, Molly (2018)
This paper takes the EDEN ISS project as example to demonstrate how findings from greenhouse tests and a 12- month mission simulation in Antarctica can inform the design for a future lunar or Martian exploration greenhouse and presents design solutions. EDEN ISS, a four-year EU-H2020 project coordinated by the German Aerospace Center Bremen, is a Ground Demonstration of Plant Cultivation Technologies for Safe Food Production in Space. EDEN ISS project partners developed an advanced nutrient delivery system, a high-performance LED lighting system, a bio-detection and decontamination system and food quality and safety procedures and technologies. A mobile two-container-sized greenhouse test facility was built to demonstrate and validate different key technologies and procedures necessary for safe food production within a (semi-)closed system. EDEN ISS is currently installed next to the German Neumayer Station III in Antarctica and serves as an over-winter-test-bed for providing fresh vegetables to the crew's diet. Intermediate outcomes from the Antarctic test include engineering, technology and crew experience facts and will inform the extra-terrestrial greenhouse design. The paper outlines the current research and expedition status and references design concepts for exploration greenhouses which are relevant to the further development of EDEN ISS into a concept for future mission exploration on the moon and on Mars. The reference examples will serve as input to the concurrent design study planned for January 2019 where the team around DLR, Thales Alenia Space and LIQUIFER Systems Group will convene to finalise the EDEN ISS project from a future perspective point of view. They will look at integrating lessons learnt for architectural aspects, system performance, crop yield, crew acceptance and contamination. Concurrent engineering, used as methodology, will support the synthesis of the findings and at the same time will ensure the reflection of this information in the design proposals.